User-friendly [(diglyme)NiBr2]-catalyzed direct alkylations of heteroarenes with unactivated alkyl halides through c?h bond cleavages - Ackermann, Lutz; Punji, Benudhar; Song, Weifeng (Advanced Synthesis & Catalysis, 2011)
A nitrogen and phosphorus ligand-free catalytic system derived from inexpensive [(diglyme)NiBr2] allowed for efficient direct C[BOND]H bond alkylations of heteroarenes with unactivated β-hydrogen-containing alkyl halides under basic reaction conditions.